2016
DOI: 10.14202/vetworld.2016.1381-1385
|View full text |Cite
|
Sign up to set email alerts
|

Studies on alterations of clinical and hemato-biochemical parameters before and after treatment in calves naturally infected with theileriosis

Abstract: Aim:The aim was to determine hemato-biochemical alterations and to determine the better treatment of theileriosis in naturally infected calves.Materials and Methods:A total of 74 Holstein crossbred calves below 6 months of age, of either sex were included for present investigation in Bikaner. Based on the clinical examinations and laboratory results, 20 calves included for hemato-biochemical studies (before and after treatment) and divided into two groups (having 10 calves each).Results:The clinical examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Variations in the hematological profile are often found, even in the same type of livestock. Hematological profiles can vary which are affected by feed, age, sex, breed, genetics, livestock health status, height of breeding site, season, environmental climate (temperature, humidity, and rainfall), physiological status of livestock, reproductive status, presence of infection, blood collection methods, and hematological profile measurement techniques used (Roland et al, 2014;Sonjaya, 2013;Yaqub et al, 2013;Ahmadi-Hamedani et al, 2014;Mazullo et al, 2014;Oramari et al, 2014;Kachhawa et al, 2016;Mariana et al, 2019). Beef cattle have a higher number of erythrocytes compared to dairy cows.…”
Section: Advances In Animal and Veterinary Sciences January 2020 | Vomentioning
confidence: 99%
“…Variations in the hematological profile are often found, even in the same type of livestock. Hematological profiles can vary which are affected by feed, age, sex, breed, genetics, livestock health status, height of breeding site, season, environmental climate (temperature, humidity, and rainfall), physiological status of livestock, reproductive status, presence of infection, blood collection methods, and hematological profile measurement techniques used (Roland et al, 2014;Sonjaya, 2013;Yaqub et al, 2013;Ahmadi-Hamedani et al, 2014;Mazullo et al, 2014;Oramari et al, 2014;Kachhawa et al, 2016;Mariana et al, 2019). Beef cattle have a higher number of erythrocytes compared to dairy cows.…”
Section: Advances In Animal and Veterinary Sciences January 2020 | Vomentioning
confidence: 99%
“…Saritha et al (2016) also performed whole blood transfusion in a calf having anaemia (3 gm/dl) due to iron deficiency and parasitism and uneventful recovery was recorded. Kachhawa et al (2016) also observed good improvement in theileriosis affected calves treated with standard treatment and single blood transfusion.…”
Section: Resultsmentioning
confidence: 68%
“…Under field conditions, haemolytic anaemia is most commonly encountered in the haemoprotozoan infections in cattle and buffaloes (Singh et al, 2014;Bhosale et al, 2020). The tickborne haemoprotozoan diseases of cattle are causing heavy economic losses to farmers due to high morbidity, mortality and reduced production in recovered animals (Kachhawa et al, 2016). The projected annual economic loss due to tropical theileriosis and babesiosis in India are INR 8092 and 580.16 crore, respectively (Narladkar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2,14,16 Erythrocytic infection with associated hemolytic anemia contributes to the pathogenesis through poorly understood mechanisms. 24,25,50 Based on recent 18S rRNA phylogenies, most of the known transforming Theileria spp. occur in the T. taurotragi clade.…”
mentioning
confidence: 99%
“…2,14,16 Erythrocytic infection with associated hemolytic anemia contributes to the pathogenesis through poorly understood mechanisms. 24,25,50…”
mentioning
confidence: 99%